Optimization of Culturomics Strategy in Human Fecal Samples - Chang, Yuxiao; Hou, Fengyi; Pan, Zhiyuan; Huang, Zongyu; Han, Ni; Bin, Lei; Deng, Huimin; Li, Zhengchao; Ding, Lei; Gao, Hong; Zhi, Fachao; Yang, Ruifu; et al. (Frontiers in Microbiology, 2019)
Most bacteria in the human gut are difficult to culture, and culturomics has been designed to overcome this issue. Culturomics makes it possible to obtain living bacteria for further experiments, unlike metagenomics. However, culturomics is work-intensive, which prevents its wide application. In this study, we performed a 30-day continuous enrichment in blood culture bottles and cultured bacterial isolates from pre-cultures removed at different time points. We compared the bacteria isolated from the enriched culture with or without adding fresh medium after each pre-culture was removed. We also compared “experienced” colony picking (i.e., picking 2 to 3 colonies for each recognized colony type) and picking all the colonies from each plate. In total, from five fecal samples, 106 species were isolated, including three novel species and six that have not previously been isolated from the human body. Adding fresh medium to the culture increased the rate of bacterial species isolation by 22% compared with the non-supplemented culture. Picking all colonies increased the rate of bacterial isolation by only 8.5% compared with experienced colony picking. After optimization through statistical analysis and simulation, sampling aerobic and anaerobic enrichment cultures at six and seven time-points, respectively, is likely to isolate >90% of bacterial species, reducing the workload by 40%. In conclusion, an extended enrichment step ensures isolation of different bacterial species at different time-points, while adding the same quantity of fresh medium after sampling, the experienced picking and the optimized time-points favor the chance of isolating more bacterial species with less work.